(3JGL GdeaQb aj JMdjI YdeGA GdeTQbs - (3NGdO Hf YjSi Hf CMeO Hf EHQGgje Hf CHj NGdO GdHdhqj, CHh GdHbGA,J (B767 (3g` s
(3ChdgG (B:s
(3hbGd hEPG LYdfG GdHjJ eKGHI ddfGS s
(3BNQgG (B:s
(3MPaJge GNJUGQkG hGbJUQJ Ydi ef PcQJ gfG s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B97s
Keywords: (3GdLZQGajG h GdHdOGfs